2023
DOI: 10.1126/scitranslmed.abq5068
|View full text |Cite
|
Sign up to set email alerts
|

A root cause analysis to identify the mechanistic drivers of immunogenicity against the anti-VEGF biotherapeutic brolucizumab

Abstract: Immunogenicity against intravitreally administered brolucizumab has been previously described and associated with cases of severe intraocular inflammation, including retinal vasculitis/retinal vascular occlusion (RV/RO). The presence of antidrug antibodies (ADAs) in these patients led to the initial hypothesis that immune complexes could be key mediators. Although the formation of ADAs and immune complexes may be a prerequisite, other factors likely contribute to some patients having RV/RO, whereas the vast ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Some of these factors include stability issues with brolucizumab, immune responses to the resulting substance, preexisting antidrug antibody responses, and immune complexes (drug/antidrug antibody) that may be associated with endothelial activation and/or induce cytokine release and platelet aggregation. 28 The incidence of IOI is presumably higher in women because of the sex difference in inflammatory stress mechanisms and in the functioning and response of the immune system. 29 This leads to variations in how males and females react to infections and vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these factors include stability issues with brolucizumab, immune responses to the resulting substance, preexisting antidrug antibody responses, and immune complexes (drug/antidrug antibody) that may be associated with endothelial activation and/or induce cytokine release and platelet aggregation. 28 The incidence of IOI is presumably higher in women because of the sex difference in inflammatory stress mechanisms and in the functioning and response of the immune system. 29 This leads to variations in how males and females react to infections and vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the immunogenicity of brolucizumab, an antibody used for the treatment of neovascular age-related macular degeneration, resulted in ADAs that were associated with the development of retinal vasculitis/retinal vascular occlusion (RV/RO) in some patients. Formation of immune complexes with brolucizumab is a proposed mechanism for RV/RO induced in some patients through cellular responses such as enhanced antigen presentation, platelet aggregation, endothelial cell activation, and cytokine release [ 15 ].…”
Section: The Clinical Consequences Associated With Immunogenicity Of ...mentioning
confidence: 99%
“…Although epitope mapping to determine ADA binding is challenging due to the polyclonal nature of ADAs, knowledge of potential B cell epitopes can be used to reduce the immunogenicity of future protein therapeutics. For example, a short amino acid sequence within brolucizumab similar to that of a bacterial protein antigen was identified through a peptide-scanning approach [ 15 ]. This suggests that the ADA response toward brolucizumab was due to preexisting antibodies against this bacterial epitope.…”
Section: In Vitro Approaches To Predicting Immunogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, after treatment with this LBL MN-rhEGF patch, the wound bed contracted in good condition and the intact epithelium layer formed. In addition, CD31, known as platelet endothelial cell adhesion molecule-1 (PECAM-1), 47 is a biomarker of vascular endothelial differentiation and becomes employed to indicate the existence of endothelial tissue and evaluate angiogenesis. 48 The immunohistochemical results of CD31 (Figure 6b) showed that treatment methods of all three groups induced the formation of blood microvessels from the wound tissue of the rats back at different degrees.…”
Section: The Rhegf Release Kinetics In Vitro Mediated By the Lbl Mn P...mentioning
confidence: 99%